Thermodynamic investigation of promethazine, loratadine, cetirizine and buclizine as antihistamine drugs; monte carlo and semi-empirical studies - Zakeri, Mina; Monajjemi, Majid; Ebrahimi, Ali (Nexo Revista Científica, 2020)
In this article, we discussed about four antihistamine drug called promethazine, loratadine, cetirizine and buclizine. Promethazine in this list is the only one in first generation antihistamine classification with CNS sedation effect and the other three belongs to second generation antihistamine group which are non-sedation and used to treat in many different anti-allergenic fields. In the following we optimized potential, kinetic and total energy of these molecules at body temperature (310 k˚) and environment temperature (298 k ˚) using Mont Carlo method in Amber force field in 500 ns. The quantum mechanics calculations and molecular structure of these molecules investigated using B3LYP level of theory with 6-31 G (d) as a basis set. Theoretical computations were performed to study thermodynamic parameters and frequency analysis. Electronic, thermal, zero point and gibs free energy and enthalpy were estimated in frequency analysis. Semi empirical computations were summarized to pm3 method and different energy parameters (total energy, Binding Energy, Isolated Atomic Energy, Electronic Energy, Core–Core Interaction and Heat of Formation.